2006
DOI: 10.1007/s10561-005-1968-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Human Ovarian Tissue

Abstract: New and often aggressive treatment schemes allow the successful healing of many young patients with cancer, but the price the young women have to pay is high: many of them lose ovarian function and fertility. Due to the improved long-term survival of adolescents and young women with malignancies undergoing gonadotoxic chemotherapy, preservation of future fertility has been the focus of recent ubiquitarian interest. A feasible solution is the cryopreservation of ovarian tissue. Ovarian tissue, after thawing, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Such findings could be due to the deleterious effect of cryopreservation on the ovarian stroma [5,[31][32][33][34][35] and granulosa cells [32,36,37], since these cell populations are directly involved in the formation of the theca layer. During follicular development, granulosa cells stimulate the differentiation of stromal cells into theca cells [38,39] through expression of different factors, such as kit ligand [40] and insulin-like growth factor (IGF)-I and/or -II [41].…”
Section: Antral Follicle Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings could be due to the deleterious effect of cryopreservation on the ovarian stroma [5,[31][32][33][34][35] and granulosa cells [32,36,37], since these cell populations are directly involved in the formation of the theca layer. During follicular development, granulosa cells stimulate the differentiation of stromal cells into theca cells [38,39] through expression of different factors, such as kit ligand [40] and insulin-like growth factor (IGF)-I and/or -II [41].…”
Section: Antral Follicle Populationmentioning
confidence: 99%
“…During follicular development, granulosa cells stimulate the differentiation of stromal cells into theca cells [38,39] through expression of different factors, such as kit ligand [40] and insulin-like growth factor (IGF)-I and/or -II [41]. Although the immature oocyte appears to be well maintained after cryopreservation [32,36], different studies have reported that the freezing procedure negatively affects stromal cells [31][32][33][34][35] and granulosa cells [32,36,37]. It might therefore be expected that death of the theca cell precursor population and granulosa cells that express factors involved in the differentiation process could have a detrimental effect on the formation of the theca cell layer.…”
Section: Antral Follicle Populationmentioning
confidence: 99%
“…Most of authors observed a reduction of normal follicles in frozen/thawed ovarian tissue compared with fresh control when using similar freezing protocols in the mouse (Candy et al, 1997), the goat (Rodrigues et al, 2004), the cow , and the ewe (Demirci et al, 2002). As for the queen, no morphological difference was observed in human follicles before and after cryopreservation (Hovatta et al, 1996;Fabbri et al, 2006) Newton observed similar proportions of "viable" follicles after freezing when using DMSO, ethylene glycol or PROH and xenografting (Newton et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…If samples are thawing slowly, ice crystals can form and/or grow causing more damage; however, if samples are thawed rapidly enough, there is little time for ice nucleation and growth to occur (Fabbri, 2006;Fabbri et al, 2006).…”
Section: Cryobiology Fundamentsmentioning
confidence: 99%